The essential inclusion of qualitative research in Administration Sciences (Revista Electrónica Calidad en la Educación Superior, 2020)
The efforts –not necessarily the achievements– of Costa Rican administrative reform are several for decades, including a thematic variety in which case management of public budgets is not exception. Thus, is vital understand that the current financial management system, result of these reform efforts, is part integral part of macro system of public administration, and as such, bears an unavoidable and interchangeable responsibility within the entire state scheme: managening the budgetary resources that make possible the national development in any of the fields of administrative activity that the citizens and inhabitants of the country require.
Keywords: administrative science, pedagogical model, curriculum, CONARE